Media Pembelajaran Interaktif Artyculate Storyline Meningkatkan Motivasi Dan Kompetensi Belajar Peserta Didik Pada Saat Pembelajaran Jarak Jauh - Agung Triono (Pusdikra Publishing, 2021)
The low motivation and competence of students in distance learning is because teachers have not used interesting learning media in the learning process. This has an impact on the learning outcomes to be achieved. Overcoming these problems the author uses the interactive learning media Artyculate Storyline to increase the motivation and learning competence of students. This interactive learning media can be used as a learning resource and support distance learning, as well as helping to facilitate the delivery of material with additional competency features, quizzes, learning videos, and glossaries that can be accessed offline and online with ease of use on the web that has been provided. This interactive learning media is also declared effective and can increase the competence of students by 5.39%. The author also creates an interactive learning media Articulate Storyline and applies it in learning process